2021
DOI: 10.1021/acs.jafc.1c03228
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of DHA with Different Molecular Forms for Ameliorating Osteoporosis by Promoting Chondrocyte-to-Osteoblast Transdifferentiation in the Growth Plate of Ovariectomized Mice

Abstract: Osteoblasts play a key role in bone remodeling. Recent studies have reported that some hypertrophic chondrocytes co-expressing collagen I(Col I) and collagen X (ColX) could directly transdifferentiate into osteoblasts during endochondral ossification. However, whether nutrition intervention is beneficial to this transformation to improve osteoporosis (OP) remains unknown. In this study, ovariectomy (OVX)-induced OP mice were orally administered with docosahexaenoic acid (DHA) in different molecular forms for 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 47 publications
(86 reference statements)
3
13
0
Order By: Relevance
“…So, it opens the possibility of cell therapy that can transform the whole tissue into desired cell types. Direct conversion at the tissue level could alleviate impaired balances between adipogenesis and osteogenesis occurred in osteoporosis [ 74 76 ], by targeting increased portion of adipose tissue in the bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…So, it opens the possibility of cell therapy that can transform the whole tissue into desired cell types. Direct conversion at the tissue level could alleviate impaired balances between adipogenesis and osteogenesis occurred in osteoporosis [ 74 76 ], by targeting increased portion of adipose tissue in the bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative real-time PCR was performed as described previously. 4 Total RNA was extracted from femur tissue with TRIzol reagent. The RNA (1 μg) of each sample was reverse transcribed into cDNA.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Zhang et al found that DHA separated from squid roe attenuated osteoporosis in ovariectomized mice. 4 Xia et al reported that supplementation with phosphorylated peptides from Antarctic krill prevented bone loss in ovariectomized mice. 5 It is generally accepted that adult bone mass is maintained by a balance of the activities of osteoblasts and osteoclasts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteoporosis, a metabolic skeletal disorder that results from the imbalance between bone formation and bone resorption, generally occurs in postmenopausal women and older people [ 1 ]. The process of bone remodeling is participated by mainly osteoclasts and osteoblasts, together with other cells including osteocytes, bone lining cells, monocytes, chondrocytes, hematopoietic stem cells, and mesenchymal stem cells (MSCs) [ 2 , 3 , 4 ]. Owing to the complicated pathology and uninhibited signaling pathway of osteoporosis, the development of medications is floundering.…”
Section: Introductionmentioning
confidence: 99%